Understanding online anonymity. - Sardá, Thais; Natale, Simone; Sotirakopoulos, Nikos; Monaghan, Mark (Media, Culture & Society, 2019)
Whenever we navigate the Web, we leave a trace through our IP address, which can in turn be used to establish our identity – for instance, by cross-checking it with a user's Internet subscription. By using software such as VPN and Tor, however, it might be possible to avoid leaving such traces. A lively debate among policymakers, security professionals, hacker communities, and human rights associations has recently ensued regarding the question if such anonymity is acceptable and in which form. This article introduces the Crosscurrent special section dedicated to this topic by providing a brief overview of this debate and by pointing to the necessity of considering online anonymity from multiple, interrelated perspectives. By taking into account both technical and social dimensions, we argue that online anonymity should not be conceptualized in absolute terms but as an inherently fluid and transitional condition that characterizes any kind of social interaction online.